Comparative investigation on the adhesion of hydroxyapatite coating on Ti–6Al–4V implant: A review paper - Mohseni, E.; Zalnezhad, E.; Bushroa, A.R. (Elsevier, 2014)
Hydroxyapatite (HA) has been used in clinical bone graft procedures for the past 25 years. Although a biocompatible material, its poor adhesion strength to substrate makes it unsuitable for major load-bearing devices. Investigations on various deposition techniques of HA coating on Ti–6Al–4V implants have been made over the years, in particular to improve its adhesion strength to the metal alloy and its long-term reliability. This review comprehensively analyzes nine techniques mostly used for deposition of HA onto Ti–6Al–4V alloys. The techniques reviewed are Plasma sprayed deposition, Hot Isostatic Pressing, Thermal Spray, Dip coating, Pulsed Laser deposition (PLD), Electrophoretic deposition (EPD), Sol–Gel, Ion Beam Assisted deposition (IBAD), and Sputtering. The advantages and disadvantages of each method over other techniques are discussed. The adhesion strength and the factors affecting the adhesion of HA coating on Ti–6Al–4V implants are also compared.